STAKEHOLDERS' PERCEPTION OF ADEQUACY OF TECHNOLOGY EDUCATION PROGRAMME IN NIGERIAN UNIVERSITIES FOR ACQUISITION OF REQUISITE EMPLOYABLE SKILLS BY STUDENTS (NAU Journal of Technology and Vocational Education, 2024)
The study was carried out to determine stakeholder's perception of adequacy oftechnology education programme in Nigerian Universities for acquisition of requisiteemployable skills by students. Three research questions guided the study and two nullhypotheseswere tested at0.05 level of significance. Descriptive survey research design was used for the study. Avalidated questionnaire with reliability coefficient of 0.73 was used for data collection. Thepopulation was made up of 227 technology education students, 57 trainers and 33employers of technology education graduates from the three zones that make up northernNigeria. Both multi-stage and purposive sampling techniques were used resulting to asample size of 188 respondents (128 students, 37 trainers and 33 employers, drawn fromthree universities. Mean and standard Deviation were used to answer the researchquestions using a benchmark of 2.50 as an index for agreement and to determine thehomogeneity or otherwise of the respondents. z-Test was used to test the two nullhypotheses. The findings showed that the technology education programme in Nigerianuniversitiesis adequate for equipping students with theappropriategeneric skillsregardlessof their stress areas. The programme wasfound not adequate for equipping the studentswith the skills needed for industrial work and self- reliance among others. Based on thefindings the researcher recommended among others that curriculum planners shouldintegrate more professional technology education courses on emerging problems intechnology education into the programme to complement the employability skills.